Kemiskinan Multidimensi dan Ketahanan Pangan: Analisis Multilevel di Kalimantan - Pujiwati, Lina Agustina; afriyanni, afriyanni; Harfina, Dewi; Fatoni, Zainal (UI Scholars Hub, 2025)
Food security is a crucial issue for sustainable development and is highly influenced by multidimensional poverty. This study measures food security and multidimensional poverty in Kalimantan Island, analyzes the determinants of household food security through a multilevel approach, and explores the influence of multidimensional poverty and regional context on food security. Data were obtained from the March 2022 National Socio-Economic Survey, comprising 33,201 households and integrated with district-level characteristics. Multidimensional poverty was measured using the Alkire-Foster method, while food security was measured based on energy consumption and the proportion of food expenditure. A multilevel ordinal logistic regression was employed to examine both household and regional determinants. The results showed that 46.6% of households were food secure, while the rest were either vulnerable or food insecure. Household head education, saving ownership, and internet access significantly increased the likelihood of food security, while households with more than four members and multidimensional poor have a higher risk of food insecurity. At the regional level, agricultural villages and poor road conditions exhibited negative correlation with food security. Based on these findings, policies are recommended to strengthen food security through multidimensional poverty alleviation, green economic development, and infrastructure enhancement of regions that support the IKN.